(untitled) (ACME, 2024)
This paper deals with one of the most transversal phenomena in numerous languages, both ancient and modern: the designation of the different parts of a vase with the same lexicon used for the parts of the human body. Focusing on four of the most commonly used modern languages in archaeological bibliography (Italian, English, French and German) and on the two classical languages par excellence (Greek and Latin), the work provides an overview of the lexicon used and the metaphors or rhetorical figures that include the figure of the vase and its parts in the ancient and modern world. In a second moment, case studies are presented, again referring to the ancient and contemporary world: on the one hand, the association of vases with the human body in archaic Greece and the case of the Etruscan canopic vessels; on the other hand, the exceptional examples of the production of anthropomorphic vases or the complete assimilation of some Central African peoples (Yungur, Mafa and Bulahay) between ceramics and the human body in the surface treatment. This article concludes by proposing some interpretative hypotheses of the phenomenon, the basic elements of which can be found both in certain cosmogonic narratives of antiquity and in the studies of cognitive linguistics of recent decades.